Quantifying Mesophotic Fish Assemblages of Hawai‘i’s Au‘au Channel: Associations With Benthic Habitats and Depth - Boland, Raymond C.; Hyrenbach, K. David; DeMartini, Edward E.; Parrish, Frank A.; Rooney, John J. (Frontiers in Marine Science, 2022)
Mesophotic reefs (30–150 m) occur in the tropics and subtropics at depths beyond most scientific diving, thereby making conventional surveys challenging. Towed cameras, submersibles, and mixed-gas divers were used to survey the mesophotic reef fish assemblages and benthic substrates of the Au‘au Channel, between the Hawaiian Islands of Maui and Lānaʻi. Non-parametric multivariate analysis: Non-metric Multidimensional Scaling (NMDS), Hierarchal Cluster Analysis (HCA), Multi-Response Permutation Procedure (MRPP), and Indicator Species Analysis (ISA) were used to determine the association of mesophotic reef fish species with benthic substrate and depth. Between 53-m and 115-m depths, 82 species and 10 genera of fish were observed together with 10 types of benthic substrate. Eight species of fish (Apolemichthys arcuatus, Centropyge potteri, Chaetodon kleinii, Chromis leucura, Chromis verater, Forcipiger sp., Naso hexacanthus and Parupeneus multifasciatus) were positively associated with increasing depth, Leptoseris sp. coral cover, and hard-bottom cover, and one species (Oxycheilinus bimaculatus) of fish was positively associated with increasing Halimeda sp. algae cover. Fish assemblages associated with rubble were peripherally associated with sand, Montipora sp. coral beds, and Leptoseris sp. coral bed fish assemblages, but not with fish assemblages associated with hard bottom. The patterns in the data suggested two depth assemblages, one “upper mesophotic” between 53 m and 95 m and the other deeper, possibly part of a “lower mesophotic” assemblage between 96 m and 115 m at the edge of the rariphotic and bottomfish complex.